Pacto Nacional Pela Alfabetização na Idade Certa (PNAIC) : as vozes de professoras sobre a formação continuada e as práticas escolares em matemática - Callejas, Ieda Maria Valle Monteiro (2017)
The present research aims to investigate "what the teachers say about the National Pact for Literacy in the Right Age (PNAIC) and the processes of teaching and learning Mathematics in the first cycle of EF". The PNAIC is a program established by the federal government through Law 12,801 / 2013, with the main focus being the continuing education of teachers, with the aim of teaching children and adolescents up to the age of eight at the end of the first cycle of Elementary School. The references that support the investigation and analysis of data are based on the studies on Mathematics in childhood, in D'Ambrósio (1999, 2004); Nacarato, Mengali and Passos (2011); Moura (2007, 2010) and Palma (2010). In discussions about continuing education, we refer to Nóvoa (1992); Garcia (1999); Imbernón (2010); Tardif (2009) and Gatti (2011). The research is based on a qualitative approach of the case study type, supported by studies by Bogdan and Biklen (1994) and Stake (2012). We investigated the reports of three effective teachers of the municipal education network of Cuiabá-MT, who work in the 1st, 2nd and 3rd years of elementary school. As sources of data production with characterization questionnaires, observations with records in field diaries, semi-structured interviews and school documents. In conducting the analyzes, we organized the data into three axes: What as a teacher about your career prospects; As voices of the teachers about a formation of the PNAIC Mathematics and The voices of the teachers about the school practices and learning processes and to teach Mathematics after a formation of the PNAIC. The data indicate that as teachers they point out positive aspects, such as: an organization of learning rights, an organization of lessons from the didactic sequence and the contribution of teaching games to learning. The highlights of the reports were for the games and the didactic sequence, both of which lack further studies and reflections for their consolidation in the pedagogical practice of the teachers. They criticize the development of the training, the short time allocated to carry out the planned activities and the articulation with the school managers, as well as the delay in access to the activity books. From this, we conclude that for a continuing training program to be effective it is necessary to start from the needs presented by the teachers themselves. In addition, the pedagogical coordinator must assume a central role as articulator of the formative actions in order to promote the development of the pedagogical team as a whole.